Microstructural Features of Spray‐Deposited Cold Rolled Al Alloy. Issue 1 (23rd February 2023) - Mittal, Rashmi; Sehrawat, Rajeev; Reddy, Bandi Venkata Ramana; Tyagi, Deepak; Sharma, Anil
Abstract: In the present work, the microstructural studies of spray deposited Al‐6Si alloys with different lead content are conducted for 0% and 40% of rolling deformation. SEM and Optical micrographs are taken for different percentage of lead content. Fine equiaxed grain morphology is observed with a uniform distribution of Pb and Si phase in an Al‐matrix and it is found from the microstructures that the size of Pb particles increased with the increase in Pb content. Grains are stretched out in the rolling direction after cold rolling. Pore size is found to decrease after 40% rolling reduction, however, it is increased with the increase in Pb content.